The perfect silence: An empirical study on how ignorance and lack of critical debate effect the process of enacting tax legislation in Serbia - Kostić Svetislav V.; Vuković Danilo (Anali Pravnog Fakulteta u Beogradu)
In this paper the authors deal with the crucial question of the ability of the Serbian institutions and society to apply adequate scrutiny with respect to the enactment of tax legislation. After providing a description of the current Serbian law-making and public consultations framework, and analyzing the relevance of the transitional nature of the Serbian political environment on the approach to the business of legislating, the authors choose three case studies which lead to the conclusion that it is the lack of even basic knowledge regarding taxation, at the level of the members of parliament and the media, combined with the silence and inertness of Serbian professional circles to participate in public debates on tax policy, that is enabling many questionable norms to enter Serbian legislation without any notable opposition or deliberation. Finally, the authors propose certain measures that could improve the public consultations process.